Association of Leukocyte, Erythrocyte, and Platelet Counts with Metabolic Syndrome and Its Components in Young Individuals without Overt Signs of Inflammation: A Cross-Sectional Study - Šebeková, Katarína; Gurecká, Radana; Podracká, Ľudmila (Children (Basel), 2024)
The presence of metabolic syndrome (MetS) increases the risk of developing type 2 diabetes, cardiovascular diseases, and mortality. MetS is associated with increased leukocyte or erythrocyte counts. In 16- to 20-year-old males (n = 1188) and females (n = 1231) without signs of overt inflammation, we studied whether the presence of MetS and its components results in elevated blood cell counts. The leukocyte, erythrocyte, and thrombocyte counts significantly but weakly correlated with the continuous MetS score, MetS components, uric acid, and C-reactive protein levels both in males (r = −0.09 to 0.2; p < 0.01) and females (r = −0.08 to 0.2; p < 0.05). Subjects with MetS had higher leukocyte (males: 6.2 ± 1.3 vs. 6.9 ± 1.2 × 109/L; females 6.6 ± 1.5 vs. 7.5 ± 1.6 × 109/L; p < 0.001), erythrocyte (males: 5.1 ± 0.3 vs. 5.3 ± 0.3 × 1012/L; females: 4.5 ± 0.3 vs. 4.8 ± 0.3 × 1012/L; p < 0.001), and platelet counts (males: 245 ± 48 vs. 261 ± 47 × 109/L; females: 274 ± 56 vs. 288 ± 74 × 109/L; p < 0.05) than those without MetS. With the exception of platelet counts in females, the blood counts increased with the number of manifested MetS components. Phenotypes with the highest average leukocyte, erythrocyte, or platelet counts differed between sexes, and their prevalence was low (males: 0.3% to 3.9%; females: 1.2% to 2.7%). Whether functional changes in blood elements accompany MetS and whether the increase in blood counts within the reference ranges represents a risk for future manifestation of cardiometabolic diseases remain unanswered.